Enhancing Organizational Learning Performance through the 'KINOSA' Learning Community: A Case Study at a Senior High School in Lebak, Indonesia - Pamungkas, Aan Subhan; Soegiarto, Asep; Japar, Muhammad; Herdiati, Dian (Universitas Sultan Ageng Tirtayasa, 2024)
This study examines the impact of the